Ocean Dynamics and the Nature of Air-Sea Interactions over the North Atlantic at Decadal Time Scales - Park, Wonsun; Latif, Mojib (Journal of Climate, 2005)
The dependence of the air–sea interactions over the North Atlantic on the ocean dynamics is explored by analyzing multicentury integrations with two different coupled ocean–atmosphere models. One is a coupled general circulation model (CGCM), in which both the atmospheric and the oceanic components are represented by general circulation models (GCMs). The second coupled model employs the same atmospheric GCM, but the oceanic GCM is replaced by a fixed-depth mixed layer model, so that variations of the ocean dynamics are excluded. The coupled model including active ocean dynamics simulates strong multidecadal variability in the sea surface temperature (SST) of the North Atlantic, with a monopolar spatial structure. In contrast, the coupled model that employs an oceanic mixed layer model and thus does not carry active ocean dynamics simulates a tripolar SST anomaly pattern at decadal time scales. The tripolar SST anomaly pattern is characterized by strong horizontal gradients and is by definition the result of the action of surface heat flux anomalies on the oceanic mixed layer. The differences in the spatial structures of the dominant decadal SST anomaly patterns yield rather different atmospheric responses. While the response to the monopolar SST anomaly pattern is shallow and thermal, the response to the tripolar SST anomaly pattern involves changes in the transient eddy statistics. The latter can be explained by the strong horizontal SST gradients that affect the surface baroclinicity, which in turn affects the growth rate of the transient eddies. The differences in the atmospheric response characteristics yield completely different response patterns. In the coupled run with active ocean dynamics, the sea level pressure (SLP) anomalies exhibit a rather homogeneous pattern that resembles somewhat the East Atlantic Pattern (EAP), while a dipolar (North Atlantic Oscillation) NAO-like SLP anomaly pattern is simulated in the coupled run without active ocean dynamics.